An on-line photovoltaic monitoring system using the zigbee based wireless network / Farihah Shariff - Farihah, Shariff (2015)
The increase of global energy demand and depletion of fossil energy has brought tremendous growth in renewable energy particularly solar energy. For grid-connected photovoltaic system (PV), monitoring is considered as a crucial aspect to observe the stability and performance of the system. Various methods are used in monitoring system. The simplest method is to have data collection done in an offline manner, where data acquisition system is installed on the plant and the data are stored locally over a period of time before being manually extracted for processing. However, this restricts the effectiveness of the monitoring system, as the data are not collected in real time. For real time monitoring system, cables are commonly used to transmit data from sensors to the data acquisition system. Due to the cost and technical limitations of the data cable, the monitoring station needs to be located reasonably close to the monitored plant. Apart from being inconvenient, the use of data cable often adds capital and maintenance cost to the system. Simpler wireless connection was introduced with similar capabilities as wired monitoring system. This research proposed an online monitoring system for grid-connected photovoltaic system by integrating monitoring system with Zigbee embedded system. The system is developed using Java and C programming language. Analysis and calculation of raw data is done in real time. Parameters like temperature, irradiation, PV power output and grid inverter output are being monitored in order to study the efficiency and stability of the system. In addition to monitoring features, this system is also equipped with user friendly control function. Another advantage of this system is with availability of internet connection; the data is accessible from anywhere around the world. The system monitored 1.25 kWp grid-connected photovoltaic system located at 3rd and 4th floor of the Wisma R&D, University of Malaya in Kuala Lumpur, Malaysia. The PV panels are mounted on the 3rd floor balcony of the Wisma R&D building, while the inverter is located on the monitoring laboratory on the 4th floor. The base station, where the host PC is placed, is located at the other end of the 4th floor. Wireless monitoring system for 1.25 kWp grid-connected inverter with a simple web-based data acquisition system and its control has been developed. The system has provided an uncertainty of ≤ ±5%.